EFEKTIVITAS BUAH APEL SEBAGAI PEMBERSIH ALAMI TERHADAP DEBRIS INDEKS DAN PH SALIVA - Desi Andriyani; Lies Elina; Yenny Liesbeth Siahaan (Poltekkes Kemenkes Medan, 2025)
Cavities are the most common dental and oral health problems people experience. There are four main factors that interact with each other in caries formation, namely host, substrate/diet, bacteria/microorganisms, saliva, and time. Indirectly, saliva influences the process of caries because saliva always wets the teeth, thus affecting the environment in the oral cavity.